Outsourcing HR functions: Development of an explanatory approach to firms' (non-existent) demand for personnel services - Dorothea Alewell; Katrin Bähring; Anne Canis; Sven Hauff; Kirsten Thommes (Management Revue, 2007)
This paper develops a comprehensive explanatory approach to the outsourcing of Human Resource (HR) functions and the resulting demand or non-demand for personnel services by companies (e.g., interim management, outplacement services, consulting in the field of HR management). Starting from the deficits of approaches that currently dominate the outsourcing debate (cost accounting approach, transaction cost approach, resource-based view of the firm), a modified and expanded framework to explain outsourcing HR management/functions is presented which includes other theoretical approaches as well. On the one hand, potential costs and benefits of outsourcing HR functions are systematically analysed, incorporating so far neglected aspects. On the other hand, triggers as well as situational and structural factors which potentially influence the outsourcing decision via the perceived alternatives or via the expectations that are formed concerning cost and benefits of outsourcing HR functions are also included in the analysis.
Keywords: 650; outsourcing of HR functions; personnel services; Personalmanagement; Outsourcing